Exploring internet inclusivity and effectiveness of e-learning initiatives during the pandemic – a comparative analysis - Ehsan, Muhammad Mubashir; Zaidan, Esmat (Frontiers in Education, 2024)
The paper presents a cross-country analysis of 25 low and lower-middle-income countries to investigate the impact of COVID-19 on educational policymaking. The study utilises variables from the Internet Inclusive Index and the Digital Skills Gap Index to explore the relationship between internet access and digital skills gaps in these countries. A descriptive and correlation analysis is conducted to understand trends and associations between the variables from data for the selected countries. The analysis shows a positive correlation between internet domains and digital skills gap scores. The paper also presents insights from low and middle-income countries to understand the challenges and responses to e-learning policy during the Pandemic. The evidence from the analysis suggests that countries with higher scores on internet domains pre-pandemic were in a better position to absorb the external shocks caused by the Pandemic. The paper's findings highlight the importance of addressing the digital divide and promoting internet inclusivity in these countries to improve their ability to adapt to external shocks and ensure continuity of learning during crises such as the COVID-19 Pandemic.